ANALISIS KEKUATAN, KELEMAHAN, PELUANG, DAN ANCAMAN (SWOT) UNTUK PENENTUAN RENCANA STRATEGIS DI SMKN 2 SANGATTA UTARA - Phiniel Kurung Pabita; Laila; Siti Novi Coaliani; Nanda Putri Amelia Santoso; Dini Aulia Mahmud; Nurlaili; Usfandi Haryaka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strengths, weaknesses, opportunities, and threats in determining the strategic plan of SMKN 2 Sangatta Utara. The research employed a descriptive qualitative approach using SWOT analysis as the primary instrument to map the school’s internal and external conditions. Data were collected through in-depth interviews, observations, document analysis, and focus group discussions involving the principal, teachers, educational staff, students, and industrial partners. The findings reveal that SMKN 2 Sangatta Utara possesses significant strengths in the competencies of vocational teachers, industrial partnerships, and the availability of vocational practice facilities. Weaknesses were identified in administrative digitalization, unequal information technology competencies among educators, and limited funding for laboratory development. Opportunities arise from the increasing demand for skilled labor, government policies on vocational education revitalization, and the growth of technology-based industries in East Kalimantan. Threats include competition among vocational schools, rapid technological changes in industry, and challenges in adapting curricula to labor market demands. The school’s strategic position is located in the aggressive quadrant, indicating the necessity for expansion strategies focused on strengthening vocational learning quality, enhancing industrial partnerships, and implementing digital-based school management transformation. This study contributes conceptually to the development of a contextual SWOT-based strategic planning model for vocational schools in industrial regions.